KMT2C/KMT2D-dependent H3K4me1 mediates changes in DNA replication timing and origin activity during a cell fate transition - Deniz Gökbuget; Liana Goehring; Ryan M. Boileau; Kayla Lenshoek; Tony T. Huang; Robert Blelloch (Cell Reports)
Summary: Mammalian genomes replicate in a cell-type-specific order during the S phase, correlated to transcriptional activity, histone modifications, and chromatin structure. The causal relationships between these features and DNA replication timing (RT), especially during cell fate changes, are largely unknown. Using machine learning, we quantify 21 chromatin features predicting local RT and RT changes during differentiation in embryonic stem cells (ESCs). About one-third of the genome shows RT changes during differentiation. Chromatin features accurately predict both steady-state RT and RT changes. Histone H3 lysine 4 monomethylation (H3K4me1), catalyzed by KMT2C and KMT2D (KMT2C/D), emerges as a top predictor. Loss of KMT2C/D or their enzymatic activities impairs RT changes during differentiation. This correlates with local H3K4me1 loss and reduced replication origin firing, while transcription remains largely unaffected. Our findings reveal KMT2C/D-dependent H3K4me1 as a key regulator of RT and replication initiation, a role that likely impacts diseases associated with KMT2C/D mutations.